Characteristics of Dried Cocoa Beans (Theobroma cacao L.) Color Using Response Surface Methodology - Sri Hartuti; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi; Yudi Pranoto (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
The research aimed to study the effects of storage time of cacao fruit before fermentation, aeration rate and temperature of fermenter during fermentation on the color value of dry cocoa  beans, including the value of L *, a *, b *, chroma, hue, and RGB, and their relationship using response surface methodology.. The results showed that storage time of cacao fruits before fermentation, aeration rate and temperature of the fermenter had an influence on the color values of L *, a *, b *, chroma, hue, and RGB of dried cocoa beans produced. The highest brightness prediction value of chroma color was ± 26 obtained in the treatment of the storage time of 9-day, aeration rate of 0.4 liters/minute, and fermenter temperature of 50 ℃. Meanwhile, the highest hue prediction value was 51.8 obtained in the treatment of storage time of 9 days, aeration rate of 0.3 liters / minute, and fermenter temperature of 50 ℃. Furthermore, the RGB color of dried cocoa beans showed that the color range of R (red) and G (green) of cocoa beans after fermentation was higher when compared to cocoa beans without fermentation, while the value of color B (blue) had a different tendency showing  that dried fermented cocoa beans had a lower blue range compared to unfermented cocoa beans.